Analisis Kecemasan Matematika dalam Menyelesaikan Soal Tipe Higher Order Thinking Skill (HOTS) - Dyah Ayu Safitri; Intan Bigita Kusumawati; Soffil Widadah (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2020)
Tense feelings that are present when students solve problems in mathematics are called mathematics anxiety. In the 2013 curriculum students are required to be able to solve HOTS questions, in this case students must have ability to work on mathematic problems namely mathematics ability. The purpose of this study is to determine the level of students' mathematical anxiety classified with the level of mathematical ability of students. The type of this research is a descriptive research with using a quantitative approach. This research was conducted in the 2019/2020 school year at SMP Negeri 1 Tanggulangin in class VII 3. Subjects were determined randomly by distributing HOTS type test questions, then students were given a math anxiety questionnaire. Data analysis in this research includes: observation, data processing, drawing conclusions of students' mathematical abilities and anxiety. The results of this research showed that each level of mathematical ability of students has a tendency to vary indicators of mathematics anxiety when solving HOTS type problems, namely high mathematical ability has low mathematical anxiety, moderate mathematical anxiety has moderate mathematical anxiety, and low mathematical ability has high mathematical anxiety.